PENGABDIAN PADA MASYARAKAT TERPADU UNTUK PENGEMBANGAN AGROWISATA DURIAN DI DESA NGROPOH BERBASIS POTEMSI LOKAL - Widyanto, R Arri; Huda, Nurul; Listiyana, Afri; Anstryani, Ditya; Putra, Handika Satya; Alfiantoro, Graha (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Tanah Laut (Politala), 2020)
Ngropoh Village, Kranggan District, Temanggung Regency, has an area of 479,184 Ha consisting of 12 dusun with 5 RWs and 30 RTs, with a population of 3,230 people. The economic potential is: agriculture, plantation, animal husbandry and home industry. The main local potential is the local durian fruit, so that it can be developed into agro tourism. The problems that occur, these potentials are not optimal. The method used is: Planning, Implementation and Reporting. The results of this activity are the pioneering durian agro tourism as edupark, the label of traditional food products and souvenirs. The benefits of this activity for the people of Ngropoh Village in the form of socio-economic potential and added value in the field of science and technology are: increased sales turnover of traditional food products and a profile video of the Ngropoh village uploaded on YouTube and social media, used as marketing media.